دور قائد المدرسة في تفعيل الأنشطة الطلابية لتعزيز الثقافة الإعلامية بمدارس جدة الابتدائية - قحطاني، منصور عبد العزيز
The study aimed at identifying the role and obstacles of the school leader in activating student activities to promote the culture of media in Jeddah primary schools from the point of view of principals and teachers. The study also aimed to reveal the extent to which there are statistically significant differences between the average responses of school principals about the role and obstacles of the school leader in activating student activities to promote the culture of media culture in Jedda.11 primary schools from the point of view of principals and teachers due to the following variables: (type of education, type of school, job and experience). To achieve the previous objectives, the researcher used the descriptive method, which includes data collection, description, interpretation, analysis and measurement of what is already in place. The researcher also used the selection of a sample of ( 1 ° 1) of primary school leaders and teachers, who were chosen by the stratified random method. In collecting data, the study relied on a questionnaire prepared by the researcher. The most important results that the study reached were: The estimates of the study sample members ofleaders and teachers about ·'the status of the role of the school leader in activating student activities to promote the culture of media in Jeddah primary schools'' were in mid-level in general.The study sample members· estimates of the obstacles to the school leader's role in activating student activities to promote the culture of media were generally low. There are statistically significant differences between the arithmetic averages of the role level and the obstacles that prevent the school leader from performing his role in activating student activities to promote the culture of media due to the variables: type of education, type of school, experience. There are no statistically significant differences between the arithmetic averages according to the variable of the type of school in the field of obstacles that limit the role of the school leader .In light of the results of the study, the researcher presented a number of recommendations and proposals aimed at developing the role of the school leader in activating student activities to promote the culture of media.